Role of Aurora B and Haspin kinases in the metaphase Topoisomerase II checkpoint. Issue 4 (16th February 2021) - Johansson, M.; Azuma, Y.; Clarke, D. J.
ABSTRACT: DNA Topoisomerase II (TopoII) uses ATP hydrolysis to decatenate chromosomes so that sister chromatids can faithfully segregate in mitosis. When the TopoII enzyme cycle stalls due to failed ATP hydrolysis, the onset of anaphase is delayed, presumably to allow extra time for decatenation to be completed. Recent evidence revealed that, unlike the spindle assembly checkpoint, this TopoII checkpoint response requires Aurora B and Haspin kinases and is triggered by SUMOylation of the C-terminal domain of TopoII.